INFLUENCE OF REMELTING ON ALUMINUM ALUMINUM RAIN - Aris Budiyono; Jamasri Jamasri (Jurnal Penelitian Saintek, 2010)
The purpose  of this research is to observe the effect of remelting  on fatigue  crack growth rates of the aluminum  alloys. The material  used in this research was selected  aluminum scraps.  The material  was melt and cast at temperature  of  745°C in the metal molding, then was made specimen  according  to ASTM  E. 647. The remelting  was done three times at the same  condition.  The fatigue  crack growth  rate  testing  was performed  in a room temperature  condition with a constant load amplitude and the load ratio was maintained to be 0,3.The experiment result show that remelting can increase fatigue  crack growth rates whichwas shown by increasing ofn  exponential  values (I" remelting  was 4,4285 MFa.mo,s, 2nd4,5562 MFa.mo,s, and 3rd  4,6078 MFa.mo,5)Key words: remelting, fatigue  crack growth rates, aluminum alloys